Analysis of the Regent's Leadership Style in Improving the Performance of Civil Servants in Tana Toraja District - Suhad, Rudy Irwan; Ibrahim, Muhammad Akmal; Abdullah, Muhammad Tang (LEGAL BRIEF, 2024)
As a Motivator within each Local Government organisation, the Regent has a reliable ability to carry out management functions. The Regent as a coach, activator, director of potentials as well as a booster of ASN work enthusiasm in local government organisations in order to achieve organisational goals.  The Regent's Leadership Style will always affect ASN Performance where ASN is an important element in the success dimension of participatory, responsive and accountable regional autonomy, more independent in accordance with the principles of good governance. Each Tana Toraja Regent's style has a dominant role in each period. The research themed Analysis of the Regent's Leadership Style in Improving ASN Performance in Tana Toraja Regency, was designed with a Qualitative method to describe the phenomenon of the Regent's distinctive leadership style and how it impacts ASN performance. The locus of this research, carried out at the Regional Government of Tana Toraja Regency where the researcher is the key instrument, making actual and purposive observations and conducting interviews with informants who are considered objective and relevant. The results of this research show that in each leadership period led by 2 different Regents, there are types of situational leadership styles where there are 3 different styles, namely Bureaucratic Participatory Style, Patrenealistic Leadership Style and Decmocratic Participatory Style